Pelvis and torso kinematics and their relationship to shoulder kinematics in high-school baseball pitchers - Oliver, G. D.; Keeley, D. W. (The Journal of Strength and Conditioning Research, 2010)
The purpose of our study was, to examine the kinematics of the pelvis and torso and determine their relationship to the kinematics of the shoulder in high-school baseball pitchers. A single group, repeated-measures design was used to collect pelvis, torso, and shoulder kinematics throughout the pitching motion. Subjects threw a series of maximal effort fastballs to a catcher located the regulation distance (18.44m) from the pitching mound, and those data from the fastest pitch passing through the strike zone were analyzed. After test trials, kinematic data were analyzed using a series of descriptive statistics to identify outliers and determine the nature of the distribution before testing for the presence of relationships between the various parameters. Results indicated that for several parameters, the actions at and about the shoulder are strongly related to the actions of the pelvis and torso throughout the pitching motion. However, although pelvis and torso kinematics throughout the pitching motion were inversely related to both shoulder elevation and the plane of shoulder elevation, only the rate of axial torso rotation was significantly related to these shoulder parameters. More importantly, the rate of axial torso rotation is significantly related to these shoulder parameters in a way that may help explain the high rate of shoulder injury in high-school pitchers. Therefore, strength training should focus on developing a strong stable core including the gluteal musculature in an attempt to control the rate of torso rotation during the pitch.